2018
DOI: 10.1109/tim.2018.2806949
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Voltage Instrument Transformers Under Nonsinusoidal Conditions Based on the Best Linear Approximation

Abstract: Voltage instrument transformers are usually tested at the rated frequency. In order to assess their performance in measuring harmonic components, typically, the frequency response function (FRF) is evaluated. Therefore, this conventional characterization does not consider nonlinear effects that may have a nonnegligible impact on the accuracy, especially when the transducer under test is represented by an inductive voltage transformer (VT). In this paper, a simple procedure for the characterization of voltage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Using the BLA one can easily check the validity of the linear framework in practical applications such as, for example, operational amplifiers [7], industrial robots [5], bit-errorrate measurements in telecommunication [9], characterization of lithium ion batteries [10], control of a medical X-ray system [6], voltage instrument transformers [11], and current transformers [12]. In addition, the dependence of the BLA on the excitation power spectrum also provides some guidance for nonlinear model selection [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Using the BLA one can easily check the validity of the linear framework in practical applications such as, for example, operational amplifiers [7], industrial robots [5], bit-errorrate measurements in telecommunication [9], characterization of lithium ion batteries [10], control of a medical X-ray system [6], voltage instrument transformers [11], and current transformers [12]. In addition, the dependence of the BLA on the excitation power spectrum also provides some guidance for nonlinear model selection [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…As for the calibration, several studies are found in literature for ITs and the research is evolving and continuing every day [8][9][10][11][12][13]. In particular, among the studies, three different ways of tackling ITs' accuracy are distinguished (but not limited to them): (i) the use of compensating techniques to solve the ITs' nonlinearities; (ii) assessment of the ITs' behavior when working at off-nominal conditions; and (iii) studies based on preliminary characterization at rated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the accuracy evaluation is a critical task for all kind of electrical assets. For example, a new way of expressing uncertainty in voltage transformers (VTs) was presented by the authors of [9], while characterization and compensation techniques for their evaluation were presented by the authors of [10][11][12] (when the VT was working under non-sinusoidal condition in [10] and in a wide frequency range in [11]). An equivalent effort has been dedicated to current transformers (CTs) by the authors of [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%